Dinamika Kerjasama Keamanan Selandia Baru-Amerika Serikat Sejak Tahun 2000 - Candra, Darang Sahdana (UI Scholars Hub, 2013)
New Zealand's security relations with the United States was halted when the former's antinuclear policies during late 1980s caused the US to suspend their security commitments. However, changes in international structure affected the once-broken security relations. Since the beginning of the 21st century, rapprochement in security cooperation has occurred between New Zealand and the US. This article analyzes the underlying causes of the rapprochement through Neoclassical Realism's paradigm and balance of interest theory. Changes in international structure, especially the reemergence of China, as well as New Zealand's domestic politics reactions concerning the said changes, are the factors that shape New Zealand's rapprochement to the US. As a small state, New Zealand's respond towards the changes in international structure is supposed to be either bandwagoning or distancing. However, New Zealand chooses to bandwagon the US as well as establishing the policies of engagement with China.